Glutamine, exercise and immune function. Links and possible mechanisms - Walsh, N. P.; Blannin, A. K.; Robson, P. J.; Gleeson, M. (Sports Medicine, 1998)
Glutamine is the most abundant free amino acid in human muscle and plasma and is utilised at high rates by rapidly dividing cells, including leucocytes, to provide energy and optimal conditions for nucleotide biosynthesis. As such, it is considered to be essential for proper immune function. During various catabolic states including surgical trauma, infection, starvation and prolonged exercise, glutamine homeostasis is placed under stress. Falls in the plasma glutamine level (normal range 500 to 750 mumol/L after an overnight fast) have been reported following endurance events and prolonged exercise. These levels remain unchanged or temporarily elevated after short term, high intensity exercise. Plasma glutamine has also been reported to fall in patients with untreated diabetes mellitus, in diet-induced metabolic acidosis and in the recovery period following high intensity intermittent exercise. Common factors among all these stress states are rises in the plasma concentrations of cortisol and glucagon and an increased tissue requirement for glutamine for gluconeogenesis. It is suggested that increased gluconeogenesis and associated increases in hepatic, gut and renal glutamine uptake account for the depletion of plasma glutamine in catabolic stress states, including prolonged exercise. The short term effects of exercise on the plasma glutamine level may be cumulative, since heavy training has been shown to result in low plasma glutamine levels (< 500 mumol/L) requiring long periods of recovery. Furthermore, athletes experiencing discomfort from the overtraining syndrome exhibit lower resting levels of plasma glutamine than active healthy controls. Therefore, physical activity directly affects the availability of glutamine to the leucocytes and thus may influence immune function. The utility of plasma glutamine level as a marker of overtraining has recently been highlighted, but a consensus has not yet been reached concerning the best method of determining the level. Since injury, infection, nutritional status and acute exercise can all influence plasma glutamine level, these factors must be controlled and/or taken into consideration if plasma glutamine is to prove a useful marker of impending overtraining.